INTERPRETATION AND CONSTRUCTION: AN ADDENDUM TO THE DISCUSSION ABOUT CREATION AND APPLICATION OF LAW: AN ADDENDUM TO THE DISCUSSION ABOUT CREATION AND APPLICATION OF LAW - Spaić, Bojan (Pravni zapisi, 2021)
As part of their regular activities, courts attach meaning to legal texts to determine the normative situation of the parties to the dispute. The activity of attributing meaning to legal texts by the courts is commonly called authoritative interpretation of law. In many cases, the meaning attributed to the text by the court deviates significantly from what laymen and even lawyers would expect, and the deviations themselves are explained in different ways in legal theory. In the purpose of explanation, the terms creation and application of law, extensive and restrictive interpretation, secundum, praeter and contra legem adjudication are used. This paper introduces and explains the concepts of interpretation, construction and their relationship, as possible explanations of situations in which authoritative judicial interpretations deviate from the expectations of the professional and lay public. For this purpose, contemporary textualist and intentionalist (cognitivist) conceptions of interpretation and construction are presented and compared with contemporary skeptical (realist, antiformalist) conceptions. Despite the simplicity and intuitive acceptability of some cognitivist views, skepticism is shown to provide a better theoretical basis for considering the application and creation of rights by courts. The very distinction between interpretation and construction proves to be a useful theoretical tool for explaining the actions of courts, as well as for specifying existing theoretical distinctions.
Keywords: application of law; creation of law; legal interpretation; legal construction; cognitivism; skepticism; textualism; intentionalism